Pelatihan Peningkatan Produktivitas Tim UP2PKK dalam Memperkenalkan Batik Khas Desa Muara Jernih Kecamatan Tabir Ulu Kabupaten Merangin - Zulfina Adriani; Amirul Mukminin; Ovie Yanti; Wahyu Juari S; Nyimas Dian M (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Jambi batik has certain characteristics, its motifs or designs are related to the richness of culture and nature by reflecting Jambi's social/culture, depicting Jambi's resources and having historical value. One of them is in Merangin Regency, especially in Muara Jernih Village, Tabir Ulu District. The UP2K PKK Team of Muara Jernih Village took steps to explore local wisdom by producing batik. The batik they produce has its own regional uniqueness with the Kepayang Mabuk batik motif, Lukah Enjab Tigo batik and the Tugu Perjuangan Perang Bukit Palumun batik. This batik has begun to be widely liked and worn by residents, this will certainly be a high economic value for the PKK mothers of Muara Jernih Village who dare to take creative steps to explore the potential of the region into a productive business. However, in its development there are several problems that become obstacles in producing and introducing the existence of the batik. The identified problems concern capital, production management, labor and batik marketing. This is where the importance of increasing productivity lies. Productivity is the main goal in industrial activities. Productivity reflects public awareness of the impact of productivity on economic growth, living standards, and competitiveness. This is what drives the PPM Team from FEB UNJA to conduct a Productivity Improvement Training for the UP2K PKK Team in Introducing Batik Khas Muara Jernih Village, Tabir Ulu District, Merangin Regency, because one form of village economic development is by developing the potential and local wisdom of the village.